On the question of the structure of the pose in standard dances - He Weiming, (Theory and Practice of Physical Culture, 2023)
Introduction. By analyzing the basic techniques of standard dance, this paper clarifies that the body posture structure of standard dance is the first item of all techniques, and it is the main content of judging standard dance competitions, occupying an important position in the technical system.